Antibody effector functions in malaria and other parasitic diseases: a few needles and many haystacks. Issue 4 (24th February 2020) - Aitken, Elizabeth H; Mahanty, Siddhartha; Rogerson, Stephen J
Abstract: Many parasitic infections stimulate antibody responses in their mammalian hosts. The ability of these antibodies to protect against disease varies markedly. Research has revealed that functional properties of antibodies determine their role in protection against parasites. Investigations of antibodies against Plasmodium spp. have demonstrated a variety of functional activities, ranging from invasion inhibition and parasite growth inhibition to antibody‐dependent cellular phagocytosis and antibody‐dependent cellular cytotoxicity. These activities have been demonstrated with a large variety of parasite molecules at multiple life cycle stages, highlighting the importance of functional antibody responses in malaria. Other parasitic infections have not yet been investigated in similar detail, but these mechanisms are likely to operate in nonmalarial parasitic infections as well. In this report, we review data on the role of functional antibody responses in protection from parasitic infections, highlighting discoveries in malaria, a parasite for which our knowledge base is the most advanced. Abstract : Antibodies are important in protecting against malarial infection and disease, and may have similar roles in other parasitic infections. This review examines current knowledge on the nature and specificity of functional antibodies that may protect against malaria and parasitic infections.